2022
DOI: 10.3389/fphar.2022.837249
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Potential of Hypoxia Inducible Factors Prolyl Hydroxylase Inhibitors in Treating Nonanemic Diseases

Abstract: Hypoxia inducible factors (HIFs) and their regulatory hydroxylases the prolyl hydroxylase domain enzymes (PHDs) are the key mediators of the cellular response to hypoxia. HIFs are normally hydroxylated by PHDs and degraded, while under hypoxia, PHDs are suppressed, allowing HIF-α to accumulate and transactivate multiple target genes, including erythropoiesis, and genes participate in angiogenesis, iron metabolism, glycolysis, glucose transport, cell proliferation, survival, and so on. Aiming at stimulating HIF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 179 publications
(222 reference statements)
0
21
0
Order By: Relevance
“…Over 20 clinical trials have demonstrated that roxadustat can effectively improve anemia in patients with CKD by increasing Hb levels and regulating iron metabolism, and studies suggested that roxadustat may be available in more pathological conditions (Miao et al, 2022). The lack of real-world safety data is an obstacle to broader acceptance.…”
Section: Discussionmentioning
confidence: 99%
“…Over 20 clinical trials have demonstrated that roxadustat can effectively improve anemia in patients with CKD by increasing Hb levels and regulating iron metabolism, and studies suggested that roxadustat may be available in more pathological conditions (Miao et al, 2022). The lack of real-world safety data is an obstacle to broader acceptance.…”
Section: Discussionmentioning
confidence: 99%
“…Hydroxylation appears to be the main regulator of HIFα subunit protein stability and is controlled by HIF prolyl hydroxylases (HIF PHD) [ 146 ]. One of the major targeting prospects of iron chelators in relation to hypoxia in COVID-19 is their ability to inhibit HIF PHD, which are non-hem iron-containing dioxygenases [ 147 , 148 , 149 ]. In this context and many other cases of iron-containing enzymes, iron removal or displacement by chelators can reduce the activity of HIF PHD and increase the anti-hypoxic response, thus improving the hypoxic state of COVID-19 patients [ 150 ].…”
Section: Deferiprone Targeting Molecules and Metabolic Pathways Of Co...mentioning
confidence: 99%
“…7 The Prolyl hydroxylase domain enzymes (PHD) 1-3 and an asparaginyl hydroxylase (factorinhibiting HIF, or FIH) regulate the HIF Pathway. 15…”
Section: Hypoxia-inducible Factor Mechanism Of Actionmentioning
confidence: 99%
“…13 Prolyl hydroxylase domain (PHD) enzymes, also known as HIF-prolyl hydroxylases (HPHs), use molecular oxygen as their substrate to hydroxylate proteins. 15 Under adequate oxygen levels, HIF-α is continuously produced and promptly degraded by PHDs via hydroxylation. 16 Von Hippel-Lindau (vHL) mediates this degradation, followed by ubiquitination and proteasomal destruction.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation